Strategic MATCH FACTOR-BASED TRUCK SCHEDULING STRATEGY FOR WET MUCK HAULAGE TRANSPORT AT UNDERGROUND MINE LEVEL HAULAGE TRUCK DEEP ORE ZONE PT. FREEPORT INDONESIA: MATCH FACTOR FOR WET MUCK TRANSPORT - hurlatu, Bernadetha; Wijaya, Andi Erwin (ReTII, 2022)
Wet muck is a mixture of fine-grained material with water which is very dangerous and can damage the panel if the withdrawal is uneven. Wet muckhandling can be done with an even withdrawal according to the existing draw order. In order for the wet muck withdrawal to be evenly distributed inaccordance with the existing draw order, it is necessary to have a tool compatibility between the Load Haul Dump at the Extraction level (3126/L)and the Dump Truck at the Truck Haulage level (3076/L). The handling that can be done is by scheduling the truck, so that the muck withdrawal can run evenly according to the existing draw order. To maketruck scheduling requires data cycle time Load Haul Dump and Truck, the number of loading points that are active, then from those data a matchfactor will be generated. Based on the match factor results in Strategy 1 with poor conditions requires 19 trucks, with moderate conditions needing19 trucks and with good conditions requires 19 trucks. Then with Strategy 2 with bad conditions requires 31 trucks, with moderate conditionsrequires 28 trucks and good conditions requires 24 trucks. Then the average production produced by Strategy 1 is 72 m3 / hour, and production using Strategy 2 is 28 m3 / hour. From the results of theseproductions, it can be concluded that with Strategy 1 it is more possible to use so that the production target does not decrease and does not requirethe addition of trucks and operators. But if you still want to use Strategy 2 and then don't want to increase the number of Dump Trucks andOperators, then we have to reduce the production target below 14,796 m3 / day. Keywords : Wet muck, Dump Truck, Load Haul Dump, Match factor, Strategy, Condition.